2011
DOI: 10.1371/journal.pgen.1002289
|View full text |Cite
|
Sign up to set email alerts
|

Bmp and Nodal Independently Regulate lefty1 Expression to Maintain Unilateral Nodal Activity during Left-Right Axis Specification in Zebrafish

Abstract: In vertebrates, left-right (LR) axis specification is determined by a ciliated structure in the posterior region of the embryo. Fluid flow in this ciliated structure is responsible for the induction of unilateral left-sided Nodal activity in the lateral plate mesoderm, which in turn regulates organ laterality. Bmp signalling activity has been implied in repressing Nodal expression on the right side, however its mechanism of action has been controversial. In a forward genetic screen for mutations that affect LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 45 publications
4
53
0
1
Order By: Relevance
“…In the context of later heart development, high-resolution imaging in zebrafish has identified a role for BMPs during heart tube rotation; here, asymmetric BMP signaling differentially affects migratory behavior on one side (32)(33)(34). These latter observations, together with our data, implicate BMP signaling in early CPC migration and in cardiac morphogenesis in anamniotes and amniotes, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the context of later heart development, high-resolution imaging in zebrafish has identified a role for BMPs during heart tube rotation; here, asymmetric BMP signaling differentially affects migratory behavior on one side (32)(33)(34). These latter observations, together with our data, implicate BMP signaling in early CPC migration and in cardiac morphogenesis in anamniotes and amniotes, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…This restricts Smad1 activity and facilitates recognition by the ubiquitin ligase Smurf1 (SMAD ubiquitination regulatory factor 1), causing degradation or, alternatively, cytoplasmic retention (24)(25)(26) (29)(30)(31), as well as during the initiation of cardiac looping (32)(33)(34). Thus, we determined whether manipulation of BMP signaling activity would alter the migration behavior of prospective cardiac cells.…”
Section: Significancementioning
confidence: 99%
“…The straightforward (sfw) mutant was identified in a forward genetic screen for mutants with organ laterality defects 12 . Whereas the heart in wild-type embryos is positioned asymmetrically under the left eye at 28 h post fertilization (hpf), sfw mutants exhibit a midline heart at 28 hpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in mice, deletion of Alk2 or Alk3 in endothelial cells disrupts the formation of cardiac valves 88, 89 , deletion of BMPER , a context dependent modulator of BMP signaling, causes failure of coronary vessel remodeling 90 , and a lack of BMPR2 in endothelial cells predisposes pulmonary hypertension 91 . Similarly, in zebrafish, a lack of alk3a or alk3b causes severe disruption in cardiovascular development 92, 93 , and mutations in alk1 causes failure in cranial vessel remodeling. 94 More recently, it has been shown that BMP signaling also regulates the emergence of lymphatic endothelial cells during development.…”
Section: Jack Of All Trades?: Diverse Functions Of Bmp Signaling In Ementioning
confidence: 99%